V-Doped CoP Nanosheet Arrays as Highly Efficient Electrocatalysts for Hydrogen Evolution Reaction in Both Acidic and Alkaline Solutions - Hua, Wei; Sun, Huanhuan; Ren, Lingbo; Nan, Ding (Frontiers in Chemistry, 2020)
It is of significant necessity to explore inexpensive and high-active electrocatalysts toward hydrogen evolution reaction (HER) in both acidic and basic media. In this work, V-doped CoP nanosheet arrays supported on the carbon cloth (V-CoP/CC) are fabricated though a facile water-bath/phosphorization method. The nanoarray structure on the three-dimensional self-supporting electrode can provide a large electrochemical active surface area with more exposed active sites to accelerate the reaction kinetics. Furthermore, V doping is able to tune the electronic properties and thus enhance the intrinsic catalytic activity of CoP. Consequently, the V-CoP/CC electrode exhibits excellent electrocatalytic activities toward HER in both 0.5 M H2SO4 and 1 M KOH solutions with small overpotentials of 88 and 98 mV at a current density of 10 mA cm−2, respectively. The present work will offer a feasible way to tailor the catalytic activity by hetero-atoms doping toward HER.